2015
DOI: 10.1590/1413-8050/ea100264
|View full text |Cite
|
Sign up to set email alerts
|

Bolsa Família Ou Desempenho Da Economia? Determinantes Da Reeleição De Lula Em 2006

Abstract: ResumoEste artigo investiga os determinantes dos resultados das eleições presidenciais brasileiras de 2006, em particular o papel do programa Bolsa Família e do desempenho econômico na migração da base eleitoral de Lula para regiões menos desenvolvidas. Os resultados indicam que, entre eleitores habituais de Lula, a participação no programa não aumenta a probabilidade de voto nesse candidato em 2006. Entre eleitores habituais de outros candidatos, esse efeito é positivo. Além disso, um maior crescimento econôm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
(32 reference statements)
0
5
0
12
Order By: Relevance
“…First, effects for 2002 are stronger if estimated using solely Bolsa Escola or Bolsa Alimentação (0.15, with se = 0.059; 0.27, with se = 0.086), suggesting that summing coverage of the two programs introduces measurement error that attenuates estimated effects. Second, CCT effects in 2006 and 2010 would probably be smaller if we could discount changes in voting patterns that would have occurred simply because the PT went from being the challenger to the incumbent (Canêdo‐Pinheiro ; Zucco ). Including the vote share of the PT's presidential candidate in 2006 as a control in the estimation of the CCT effects in 2010, for instance, reduces estimates of CCT effects from 0.18 to just about 0.08 (with se = 0.023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, effects for 2002 are stronger if estimated using solely Bolsa Escola or Bolsa Alimentação (0.15, with se = 0.059; 0.27, with se = 0.086), suggesting that summing coverage of the two programs introduces measurement error that attenuates estimated effects. Second, CCT effects in 2006 and 2010 would probably be smaller if we could discount changes in voting patterns that would have occurred simply because the PT went from being the challenger to the incumbent (Canêdo‐Pinheiro ; Zucco ). Including the vote share of the PT's presidential candidate in 2006 as a control in the estimation of the CCT effects in 2010, for instance, reduces estimates of CCT effects from 0.18 to just about 0.08 (with se = 0.023).…”
Section: Resultsmentioning
confidence: 99%
“…This was soon followed by Nicolau and Peixoto () and Zucco (), with more data‐intensive studies of electoral results that found more evidence in support of a BFP electoral effect. Other studies have included geographical analysis tools (Soares and Terron ), ecological inference techniques (Canêdo‐Pinheiro ) and public opinion survey data (Licio, Castro, and Renno ) and mostly concur that CCTs had at a non‐negligible effect on voting behavior. Additional work has placed CCTs in the context of a wider political strategy to bypass local‐level politicians (Fenwick ) and has found little evidence of clientelism in the BFP (Fried ; Sugiyama and Hunter ).…”
Section: Should Voters Reward Incumbents For Targeted Social Policies?mentioning
confidence: 99%
“…Entre os diversos trabalhos que analisaram as razões do voto em Lula em 2006, é praticamente unânime a opinião de que a avaliação retrospectiva do governo, influenciada especialmente por "fatores econômicos", pesou na sua reeleição. O petista se beneficiou do crescimento econômico pequeno, porém persistente, da inflação baixa, do aumento do poder de consumo da população e, sobretudo, do Bolsa Família, programa de distribuição de renda implementado pelo seu governo (Nicolau e Peixoto, 2006;Carraro et al, 2007;Abensur, Cribari--Neto e Menezes, 2007;Rennó, 2007;Hunter e Power, 2007;Zucco, 2008;Canêdo-Pinheiro, 2009;Licio, Rennó e Castro, 2009;Singer, 2009;Marques et al, 2009).…”
Section: A Eleição Presidencial De 2006unclassified
“…O resultado da eleição presidencial brasileira de 2006 levantou alguns pontos que ganharam maior atenção de pesquisadores e analistas: o impacto dos programas de distribuição de renda do governo Lula (Partido dos Trabalhadores, PT), em especial o Bolsa Família (Abensur, Cribari-Neto e Menezes, 2007;Marques et al, 2009;Lício, Rennó e Castro, 2009;Canêdo-Pinheiro, 2009;Corrêa, 2010), e do crescimento econômico para a vitória do petista (Carraro et al, 2007); a nova configuração das bases * Versões diferentes deste artigo foram apresentadas no XIX Congresso da Compós, no IV Congresso da Compolítica e no IV Congresso Latino Americano da Wapor. Agradeço as críticas e comentários recebidos em cada um desses eventos.…”
unclassified
“…O Bolsa Família (BF) é um programa de transferência (Canêdo-Pinheiro, 2009). Existem evidências que esta migração de votos foi causada pelo programa de assistencialismo Bolsa Família, ver Zucco (2008), Carraro et al (2007) e Souza e Cribari-Neto (2013).…”
Section: Introductionunclassified